2017
DOI: 10.1001/jamaoncol.2016.3662
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Androgen Deprivation Therapy and Risk of Dementia

Abstract: Androgen deprivation therapy in the treatment of prostate cancer may be associated with an increased risk of dementia. This finding should be further evaluated in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
136
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 42 publications
4
136
6
Order By: Relevance
“…One caveat of the study is that a higher percentage of fatigued subjects received concomitant ADT (85%) compared to SF subjects (62.5%). Concomitant ADT use has been linked to impaired cognitive performance in prostate cancer patients [52, 53]. In addition, we have shown previously that ADT was a reliable clinical predictor of fatigue during radiation therapy for prostate cancer [5].…”
Section: Discussionmentioning
confidence: 99%
“…One caveat of the study is that a higher percentage of fatigued subjects received concomitant ADT (85%) compared to SF subjects (62.5%). Concomitant ADT use has been linked to impaired cognitive performance in prostate cancer patients [52, 53]. In addition, we have shown previously that ADT was a reliable clinical predictor of fatigue during radiation therapy for prostate cancer [5].…”
Section: Discussionmentioning
confidence: 99%
“…93 Studies examining the effects of ADT on cognitive functioning have yielded inconclusive results, 9497 however a meta-analysis of 14 studies concluded ADT in patients with prostate cancer had a significant impact on visuomotor ability, 98 and ADT has been associated with increased risk for dementia. 99 …”
Section: Risk Factors For Crcimentioning
confidence: 99%
“…Depression is common in patients with cancer, and men who are taking ADT may have a higher risk of depression 91 . The data suggesting that exposure to ADT is associated with an increased risk of cognitive decline are inconsistent 92–95 . While effective treatments for depression are available, there are no standardized interventions to reverse cognitive decline for this patient population.…”
Section: Resultsmentioning
confidence: 99%